2018
DOI: 10.1007/s10035-017-0781-y
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic calibration of discrete element simulations using the sequential quasi-Monte Carlo filter

Abstract: The calibration of discrete element method (DEM) simulations is typically accomplished in a trial-and-error manner. It generally lacks objectivity and is filled with uncertainties. To deal with these issues, the sequential quasi-Monte Carlo (SQMC) filter is employed as a novel approach to calibrating the DEM models of granular materials. Within the sequential Bayesian framework, the posterior probability density functions (PDFs) of micromechanical parameters, conditioned to the experimentally obtained stress-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…A novel iterative Bayesian filter is developed to estimate the posterior probability distribution of the micromechanical parameters of a DEM model, conditioned to history-dependent experimental data. The iterative application of conventional sequential Bayesian estimation [2,3] allows the virtual granular material to learn from all previous experimental measurements of the physical system being modeled in a fast and automated manner.…”
Section: Bayesian Calibrationmentioning
confidence: 99%
“…A novel iterative Bayesian filter is developed to estimate the posterior probability distribution of the micromechanical parameters of a DEM model, conditioned to history-dependent experimental data. The iterative application of conventional sequential Bayesian estimation [2,3] allows the virtual granular material to learn from all previous experimental measurements of the physical system being modeled in a fast and automated manner.…”
Section: Bayesian Calibrationmentioning
confidence: 99%
“…These results showed that the latter three factors have a significant influence on the porosity. Cheng et al [37] developed a DEM calibration approach of granular soils based on the sequential quasi-Monte Carlo (SQMC) filter. They calibrated the micromechanical parameters of the contact laws against the stress-strain behavior of Toyoura sand in drained triaxial compression conditions at different confining pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical or optimisation‐based algorithms become popular to determine particle‐scale parameters in DEM as an inverse problem. Existing algorithms include the response surface methodology, artificial neural networks, Latin hypercube sampling and Kriging, random forest, the genetic algorithm, the sequential quasi‐Monte Carlo, and the Bayesian approach . Although these algorithms are useful to quantify a wide range of complex problems, their applications alone still suffer from numerical issues such as local optimum and time‐consuming iterative process.…”
Section: Introductionmentioning
confidence: 99%